Desain Aplikasi Pedataan Pasien Pada Puskesmas Tugu Jaya Kabupaten OKI - Imam Solikhin (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
Puskesmas Tugu Jaya is a government institution that serves the public health either having a small economy or the economy up. The Puskesmas in the patient's data collection system is still done through a manual process (through paper writing) then typed in a computer using Ms.Office). The process of data collection like this is less efficient because the process of repetition is done repeatedly so long time. The process of storing, searching and reporting patient data that often occurs difficult because employees have to look for in one place. Solutions to overcome these problems by proposing the design of patient data collection application at Tugu Jaya Community Health Center of OKI-based computerized. The design of this application can be developed so that the patient data collection system at Tugu Jaya Puskesmas OKI Regency is more efficient in its processing compared to the current manual system running today. In this pedesainan need an application development method (software) in the form of linear sequential model to finish the phases to produce a design that later can dikembangankan into computerized applications. Application development is expected to be able to perform pakanendan data processing pembutan report quickly, precisely, and accurately.